DEVELOPMENT OF FISH FARMING IN BUCKETS SYSTEM AND INNOVATION OF PROCESSED PRODUCTS TO IMPROVE COMMUNITY RESILIENCE IN THE FACE OF THE COVID-19 PANDEMIC - Andri Akbar; I Gusti Putu Octavio; Rida Aini Rahmawati (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2021)
The Covid-19 pandemic has an impact in all fields, namely in terms of health, social, economic, and food. Reduced income or even job loss to cause a decrease in the ability to meet basic needs, namely family food needs. Corporate Social Responsibility (CSR) of Pertamina Corporation Integrated Terminal Jakarta initiated collaboration between community groups and various stakeholders through the integration of the budikdamber system and the development of processed product innovations done in Rawa Badak Selatan Village, Koja District, North Jakarta as the Area 1 Company's Ring. The development of processed innovation products is carried out together with the Bunda Koja group by carrying out all contain catfish product (ACE) activities. ACE's budikdamber activities are empowered by cultivating fish and vegetables in buckets carried out in several yards of residents of the Rawa Badak Selatan Village. This activity is expected to contribute to the community’s resilience in the face of pandemics by increasing knowledge and skills in developing mental systems and their processed products. The implementation of activities is carried out by training methods and the application of mentoring. The community generally feels helped because the process of making processed and ACE budikdamber is empowered to facilitate for the community to get nutritious food. This activity also has an impact on improving nutrition and socioeconomics of toddler parents, through training in nutritious catfish processed products, toddler mothers can learn to understand the importance of nutritious food for toddlers.